2016
DOI: 10.1101/mcs.a000752
|View full text |Cite
|
Sign up to set email alerts
|

Integrated clinical, whole-genome, and transcriptome analysis of multisampled lethal metastatic prostate cancer

Abstract: We report the first combined analysis of whole-genome sequence, detailed clinical history, and transcriptome sequence of multiple prostate cancer metastases in a single patient (A21). Whole-genome and transcriptome sequence was obtained from nine anatomically separate metastases, and targeted DNA sequencing was performed in cancerous and noncancerous foci within the primary tumor specimen removed 5 yr before death. Transcriptome analysis revealed increased expression of androgen receptor (AR)-regulated genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 57 publications
0
33
0
Order By: Relevance
“…Enzalutamide and ARN509 (apalutamide) have agonist effects also on the H875Y, T878A and T878S mutations, all detected in CRPC patients ( 38 ), but acquired resistance to those drugs may primarily depend on increased expression of the glucocorticoid receptor and AR bypass ( 45 , 46 ) or the induction of constitutively active AR variants, as discussed below. The T878A , H875Y and the L702H mutations have been observed in CRPC patients progressing during abiraterone treatment and associated with either the increased progesterone levels obtained after CYP17 inhibition ( 25 , 47 , 48 , 49 ) or with the co-administration of exogenous glucocorticoids given to compensate for significantly reduced cortisol levels ( 26 , 50 , 51 , 52 ). The activating AR point mutations T877A, L702H and H875Y have been detected in cfDNA from patients with CRPC and shown to be associated with resistance to abiraterone and enzalutamide ( 25 , 26 , 42 , 49 ).…”
Section: Activating Ar Mutations In Crpcmentioning
confidence: 99%
“…Enzalutamide and ARN509 (apalutamide) have agonist effects also on the H875Y, T878A and T878S mutations, all detected in CRPC patients ( 38 ), but acquired resistance to those drugs may primarily depend on increased expression of the glucocorticoid receptor and AR bypass ( 45 , 46 ) or the induction of constitutively active AR variants, as discussed below. The T878A , H875Y and the L702H mutations have been observed in CRPC patients progressing during abiraterone treatment and associated with either the increased progesterone levels obtained after CYP17 inhibition ( 25 , 47 , 48 , 49 ) or with the co-administration of exogenous glucocorticoids given to compensate for significantly reduced cortisol levels ( 26 , 50 , 51 , 52 ). The activating AR point mutations T877A, L702H and H875Y have been detected in cfDNA from patients with CRPC and shown to be associated with resistance to abiraterone and enzalutamide ( 25 , 26 , 42 , 49 ).…”
Section: Activating Ar Mutations In Crpcmentioning
confidence: 99%
“…It has been previously demonstrated that [28] that metastasis to metastasis spread of prostate tumor clones is common. This may explain the small heterogeneity seen in HRstatus of multiple metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarker driven clinical trials for mCRPC have been hampered by the difficulty of obtaining metastatic tissue (11). Also, profiling a single metastatic lesion is not capable of providing the full spectrum of the molecular heterogeneity that may exist within the patient (12,13). A liquid biopsy, either in the form of circulating tumour cells (CTCs) or tumour-derived cell-free DNA (circulating tumor DNA, ctDNA), is an attractive alternative (14,15).…”
Section: Background and Rationalementioning
confidence: 99%